Film Propaganda: Ikonografi Kekuasaan - Budi Irawanto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2004)
As a modern technological invention cinema has numerous potentialities such as economic, social and political power. Fascist regimes as well as film corporations have employed cinema as a tool of propaganda to control and mobilize the masses for the sake of their power longevity. Moreover, the character of film itself is a perfect fascist medium which came from the network of proto-fascism of the twentieth century civilization. By using various genres of Indonesian cinema from different eras as a case study, this article argues that Indonesian propaganda films have monolithic representation which can be described as a cult of